2020
DOI: 10.3390/molecules25204730
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder Additions as Mechanistic Probes–Interception of Silyl-Isoindenes: Organometallic Derivatives of Polyphenylated Cycloheptatrienes and Related Seven-Membered Rings

Abstract: The intermediacy of short-lived isoindenes, generated in the course of metallotropic or silatropic shifts over the indene skeleton, can be shown by Diels-Alder trapping with tetracyanoethylene, leading to the complete elucidation of the dynamic behaviour of a series of polyindenylsilanes. Cyclopentadienones, bearing ferrocenyl and multiple phenyl or naphthyl substituents undergo [4 + 2] cycloadditions with diaryl acetylenes or triphenylcyclopropene to form the corresponding polyarylbenzenes or cycloheptatriene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Previously it was shown that bulky aryl groups make the transition into axial isomer of heptaarylcycloheptatrienes irreversible and [1,5]-hydride shift takes place only when the initially formed equatorial conformer is long-living. 46,47 In our cases ester groups are less bulky and, moreover, alkyl groups in 9b,c afford simplified conformational flip and, thus, [1,5]-hydride shift 4 to make the more stable unsymmetrical isomer prevalent (in 9b) of equal (in 9c) under This article is protected by copyright. All rights reserved.…”
Section: Template For Synthesis Thiemementioning
confidence: 75%
See 1 more Smart Citation
“…Previously it was shown that bulky aryl groups make the transition into axial isomer of heptaarylcycloheptatrienes irreversible and [1,5]-hydride shift takes place only when the initially formed equatorial conformer is long-living. 46,47 In our cases ester groups are less bulky and, moreover, alkyl groups in 9b,c afford simplified conformational flip and, thus, [1,5]-hydride shift 4 to make the more stable unsymmetrical isomer prevalent (in 9b) of equal (in 9c) under This article is protected by copyright. All rights reserved.…”
Section: Template For Synthesis Thiemementioning
confidence: 75%
“…Pyrone derivatives have been used as four-electron components in the synthesis of cycloheptatrienes previously. 47 However, only cyclopropenone ketals gave cycloheptatriene products in the reaction conducted. In some cases, they initially generate a dipole, which in turn undergoes a (4+3)-cycloaddition with pyrones to afford a different arrangement of cyclopropene carbon atoms within the products than in direct reactions.…”
Section: Paper Synthesismentioning
confidence: 99%
“…The ready availability of the mixed benzils 1-ferrocenyl-2-aryl-1,2-dioxoethane, 89 and 92, has been shown to provide a convenient route to ferrocenyl-triaryl-cyclopentadienones, 93 that are versatile precursors to the sterically hindered arenes C 6 R 5 Fc, where R = phenyl or β-naphthyl, and the cycloheptatriene C 7 Ph 6 HFc (Scheme 29) [54,58,59].…”
Section: Benzoins and Benzilsmentioning
confidence: 99%
“…Unsurprisingly, ferrocil does not undergo the benzil-to-benzilic acid rearrangement; once again, such a process would have required the migration of a ferrocenyl unit under electronically unfavorable anionic conditions. The ready availability of the mixed benzils 1-ferrocenyl-2-aryl-1,2-dioxoethane, 89 and 92, has been shown to provide a convenient route to ferrocenyl-triaryl-cyclopentadienones, 93 that are versatile precursors to the sterically hindered arenes C6R5Fc, where R = phenyl or β-naphthyl, and the cycloheptatriene C7Ph6HFc (Scheme 29) [54,58,59].…”
Section: Benzoins and Benzilsmentioning
confidence: 99%